2013
DOI: 10.4081/ejh.2013.e11
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Amino Acid Transporter 5 is widely expressed in peripheral tissues

Abstract: It is routinely stated in the literature that Excitatory Amino Acid Transporter 5 (EAAT5) is a retina-specific glutamate transporter. EAAT5 is expressed by retinal photoreceptors and bipolar cells, where it serves as a slow transporter and as an inhibitory glutamate receptor, the latter role is due to the gating of a large chloride conductance. The dogma of an exclusively retinal distribution has arisen because Northern blot analyses have previously shown only modest hybridisation in non-retinal tissues. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…EAAT5 has also been detected in cerebellum (Ochiai et al, 2010) and tissues such as the vestibular system (Dalet et al, 2012) and testis (Lee et al, 2011a). More recent studies of EAAT5 using a newly developed antibody showed abundant expression in many non-nervous tissues including liver, kidney, intestine, heart, lung and skeletal muscle (Lee et al, 2013). Collectively, these findings dispel the widely held notion that the expression of EAAT5 is confined to the retina.…”
Section: Introductionmentioning
confidence: 85%
“…EAAT5 has also been detected in cerebellum (Ochiai et al, 2010) and tissues such as the vestibular system (Dalet et al, 2012) and testis (Lee et al, 2011a). More recent studies of EAAT5 using a newly developed antibody showed abundant expression in many non-nervous tissues including liver, kidney, intestine, heart, lung and skeletal muscle (Lee et al, 2013). Collectively, these findings dispel the widely held notion that the expression of EAAT5 is confined to the retina.…”
Section: Introductionmentioning
confidence: 85%
“…It is present in vestibular hair cells (Dalet et al, 2012), in the heart (Arriza et al, 1997;Martinov et al, 2014), in skeletal muscle (Arriza et al, 1997) and possibly at low levels in several other peripheral organs (Lee et al, 2013).…”
Section: Eaat4mentioning
confidence: 99%
“…EAAC1 is expressed in intestine, kidney, heart, lung, placenta and liver (Nakayama, Kawakami, Tanaka & Nakamura, 1996). Low levels of EAAT4 mRNA are found in placenta, and EAAT5 is expressed in liver, kidney, intestine, heart, lung and skeletal muscle (Gegelashvili et al, 1998, Lee, Anderson, Stevens, Beasley, Barnett & Pow, 2013). These differential expression patterns strongly suggest that each of these transporters is under specific transcriptional regulation.…”
Section: Differential Localization Of Glutamate Transportersmentioning
confidence: 99%